If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 4 = 4(x + -11) Reorder the terms: 4 + 7x = 4(x + -11) Reorder the terms: 4 + 7x = 4(-11 + x) 4 + 7x = (-11 * 4 + x * 4) 4 + 7x = (-44 + 4x) Solving 4 + 7x = -44 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 4 + 7x + -4x = -44 + 4x + -4x Combine like terms: 7x + -4x = 3x 4 + 3x = -44 + 4x + -4x Combine like terms: 4x + -4x = 0 4 + 3x = -44 + 0 4 + 3x = -44 Add '-4' to each side of the equation. 4 + -4 + 3x = -44 + -4 Combine like terms: 4 + -4 = 0 0 + 3x = -44 + -4 3x = -44 + -4 Combine like terms: -44 + -4 = -48 3x = -48 Divide each side by '3'. x = -16 Simplifying x = -16
| (4*r)*13= | | 7y-12y+3y= | | 4(8+m)=2m+16 | | 4+7=(3-9v) | | lnx^5/2-0.5lnx=ln25 | | 15c+7=11c+35 | | -5(-4+9x)= | | 7r=2(4r-9) | | (9y/14)/(6/14) | | -7(x+1)+7(7+x)= | | 2x+(2x-8)=72 | | X-7/8=-7/12 | | X(-2x+5)=33 | | 6m-3=1/3m | | -15=(3n/5) | | X-7/8=7/12 | | 48x-4=13x+6 | | -7+6p=-97 | | X+x+(x-4)+(x-4)=72 | | -(2r+7s)+2(r+s)= | | 12/6*5 | | x-1.6=-2.5 | | -6(a-3)-7(5-4a)= | | 1/42/7 | | -9x-11y-8x+12y= | | 14-m/2=10 | | -5x-10=2-[x+4] | | 4-5a=4(1+8a) | | 4x^2^4-16x^4/12ux^5 | | 45/17 | | 7r+5=11 | | V=3812 |